Factor determining customers' repurchase intention of healthcare insurance products - Rahman, Muhammad Sabbir; Mohamad, Osman; AbdelFattah, Fadi AbdelMuniem; Aziz, Nusrtae (2014)
This inquiry studies the empirical testing the determinant of customers’ repurchase intention of health care insurance products in Malaysia. The research was established on an empirical investigation of the existing health insurance customers from Klag valley area Malaysia. The main data for the study were generated from self-administered survey of 160 samples. Data were analysed by using descriptive and inferential statistics (Exploratory Factor Analysis). From the application of exploratory factor analysis, it was concluded that the correlation matrix was all positive and above 0.6. Three factors were extracted which explain 47% of the variation. Lastly, the variables were loaded in one part or the other showing that the variables are satisfactory for further works. As the survey is based on health insurance in particular under Malaysian perspective, its consequences may also be of interest to the managers of health insurance providers as well as policy makers to draw further strategy in their parts.